A data set characterizing thermal resistance at evaporation from sintered porous media. (October 2020) - Zimmermann, Sascha; Dreiling, Robert; Nguyen-Xuan, Thinh; Pfitzner, Michael
Highlights: Meniscus shapes in sintered porous media are calculated using Surface Evolver. Explicit expressions are used to obtain evaporation and condensation coefficients. Formation of capillary bridges significantly affect evaporation and condensation. Temperature dependent fluid properties are the key to accurate simulations. A data set of thermal resistances for application in macro simulations is provided. Graphical abstract: Abstract: Passive cooling devices like heat pipes play an increasingly important role in a vast field of cooling applications. For optimal design of heat pipe-based cooling systems, it is crucial to perform reliable simulations which adequately account for thermal resistance of evaporation from the embedded capillary structure. In this study, a data set which provides thermal resistance for water evaporating from sintered porous media was obtained using a micro model. The open source software Surface Evolver was used to calculate 1638 liquid meniscus shapes in a cubic arrangement of sintered spheres for various porosities, water levels, and contact angles. A heat conduction model accounting for temperature dependent thermophysical fluid properties was developed to compute corresponding thermal resistances. Phase change at the liquid surface was modeled using expressions based on the thermal-energy-dominant limit of the statistic rate theory. The results show a significant dependence of thermal resistance on vapor temperature, wick geometry, contact angle, and the shape of contact line. 8316 data points suggest high vapor temperatures, small grain sizes, low porosities, and small contact angles for minimal thermal resistance. Furthermore, a method for utilizing the data set in device level macro models is outlined.